Phytol metabolism in plants. (April 2019) - Gutbrod, Katharina; Romer, Jill; Dörmann, Peter
Abstract: Phytol, the prenyl side chain of chlorophyll, is derived from geranylgeraniol by reduction of three double bonds. Recent results demonstrated that the conversion of geranylgeraniol to phytol is linked to chlorophyll synthesis, which is catalyzed by protein complexes associated with the thylakoid membranes. One of these complexes contains light harvesting chlorophyll binding like proteins (LIL3), enzymes of chlorophyll synthesis (protoporphyrinogen oxidoreductase, POR; chlorophyll synthase, CHLG) and geranylgeranyl reductase (GGR). Phytol is not only employed for the synthesis of chlorophyll, but also for tocopherol (vitamin E), phylloquinol (vitamin K) and fatty acid phytyl ester production. Previously, it was believed that phytol is derived from reduction of geranylgeranyl-diphosphate originating from the 4-methylerythritol-5-phosphate (MEP) pathway. The identification and characterization of two kinases, VTE5 and VTE6, involved in phytol and phytyl-phosphate phosphorylation, respectively, indicated that most phytol employed for tocopherol synthesis is derived from reduction of geranylgeranylated chlorophyll to (phytol-) chlorophyll. After hydrolysis from chlorophyll, free phytol is phosphorylated by the two kinases, and phytyl-diphosphate employed for the synthesis of tocopherol and phylloquinol. The reason why some chloroplast lipids, i.e. chlorophyll, tocopherol and phylloquinol, are derived from phytol, while others, i.e. carotenoids and tocotrienols (in some plant species) are synthesized from geranylgeraniol, remains unclear.